The associated factors of depression and quality of life in patients with diabetic foot ulcer in Hospital Tengku Ampuan Afzan / Chan Tze Lin - Chan, Tze Lin (2016)
Diabetic foot complications are one of the common causes of lower extremity amputations. Furthermore, diabetic patients with foot ulcer have high hospitalization rates as compared with those without foot complications. Diabetic foot ulcer patients with comorbid depression have high morbidity and mortality as well as poor quality of life. However, there is limited study available in Malaysia. Objective: The primary aim was to determine the prevalence of depression in patients with diabetic foot ulcer in Hospital Tengku Ampuan Afzan and to determine the sociodemographic and clinical factors associated with depression in diabetic foot ulcer patients. The study was also to determine the quality of life and social support among diabetic foot ulcer patients and compared between the depressed and non depressed diabetic foot patients. Method: This was a cross sectional study where a total of 150 diabetic foot ulcer patients were recruited. Sociodemographic data and clinical variables were determined in diabetic foot ulcer patients. The prevalence of major depressive disorder among the diabetic foot ulcer patients was determined using Mini International Neuropsychiatry Interview (M.I.N.I). Hospital Anxiety and Depression Scale (HADS) was used as screening tool. M.I.N.I questionnaire was used as diagnostic tool. Both HADS and M.I.N.I were used for all the study subjects to confirm the validation between the positive cases of HADS with positive cases of M.I.N.I. The study also investigated the association between major depressive disorder with clinical and sociodemographic factors of diabetic foot ulcer patients. The Quality of life was assessed using the WHOQOL-BREF and social support was evaluated using Multidimensional Scale of Perceived Social Support (MSPSS). Result: The prevalence of depression in diabetic foot ulcer patients using M.I.N.I (diagnostic tool) was 20.7% and prevalence of depression based on HADS-D (screening tool) with cut off point of ≥8 was 24%. In this study, all the positive cases of M.I.N.I were also screened positive using HADS. Major depressive disorder was found to be significantly associated with the family history of depression (p=0.015, OR=8.667), another chronic medical illnesses (1-2 chronic illnesses p=0.033, OR=5.093; ≥3 chronic medical illnesses p=0.009, OR=13.200), three and more diabetes complication( p=0.025, OR=5.564). In this study, quality of life of diabetic foot ulcer patients with comorbid depression was found lower compared to those without depression. The mean total score for WHOQOL-BREF was 76.6 (SD=8.8) for diabetic foot ulcer patients with depression and 89.2 (SD=10.9) for non depressed group. In this study, all the diabetic foot ulcer patients had perceived overall good social support with mean total score 5.5 (SD=0.98). There was no significant association found between level of social support among diabetes foot ulcer patients with comorbid major depressive disorder. Conclusion: This study found a high prevalence of depression among the patients with diabetic foot ulcer. The diabetic foot ulcer with comorbid depression had significantly poorer quality of life compared to non depressed group. Medical practitioners should regularly screen high risk group for early detection of depression and improve the quality of life.